A Mouse Model of West Nile Virus Infection. Issue 4 (20th December 2017) - Graham, Jessica B.; Swarts, Jessica L.; Lund, Jennifer M.
Abstract: The use of a mouse model to study the breadth of symptoms and disease severity seen in human West Nile virus (WNV) infection can provide insight into the kinetics of the immune response and the specific pathways responsible for control of WNV infection and viral clearance. Here, we provide protocols for performing WNV infection of mice, as well as complete immunophenotyping analysis of the cellular immune response to infection in both the periphery and the central nervous system in a mouse model of WNV infection. © 2017 by John Wiley & Sons, Inc.